Attentional Blink in Pilots and Its Relationship With Flight Performance - Li, Fengzhan; Liu, Quanhui; Lu, Huijie; Zhu, Xia (Frontiers in Psychology, 2020)
Objective In flight, military pilots need to monitor changes in the external environment and monitor the situation of the aircraft at the same time. Attentional blink (AB) reflects attentional blindness in time. Therefore, the present study investigated the AB effect in military pilots and its relationship with flight performance. Methods Thirty male military pilots (44.23 ± 4.07 years old) and 29 control participants (44.07 ± 2.93 years old) underwent testing with the classic rapid serial visual presentation paradigm. The participants’ accuracy in detecting a second target stimulus (T2/T1) on the basis of their correctly response to the first target stimulus (T1) was calculated to measure the AB effect. The flight performance of these military pilots was also collected. Results The participants’ accuracy in detecting T2/T1 at positions of 180, 270, 360, and 450 ms was significantly lower than that in detecting T1 in both groups. The military pilots’ detection accuracy of T2/T1 at the positions of 180 ms (p < 0.001) and 270 ms (p < 0.001) was significantly higher than that of the control participants, and their mean detection accuracy of T2/T1 (AB effect) at the positions of 180, 270, 360, and 450 ms was also significantly higher than that of the control participants (p < 0.001). There was a significant correlation between the AB effect and the lowest flight performance score for the military pilots (r = 0.52, p = 0.004), and the regression coefficient was significant (β = 0.514, p = 0.004, R2 = 0.31). Conclusions Both groups experienced the AB effect, but the military pilots’ performance regarding the AB effect was better than that of the control participants. The AB effect can predict the lowest flight performance score in military pilots. These findings may have implications for the grounding and selection of Chinese military pilots.